Orbinia (Polychaeta: Orbiniidae) from the Brazilian coast: two new species and two new records - Leão, Luciana Sanches Dourado; Santos, Cinthya Simone Gomes (Zootaxa, 2016)
Representatives of the Family Orbiniidae are very common in marine sediments and are found in both shallow and deep waters. Currently, 26 species and 10 genera have been recorded along the Brazilian coast. The specimens examined in this study were collected at depths ranging from 25 to 400 m in the Campos Basin (20–24ºS; 39–42ºW), Rio de Janeiro, in the summer and winter of 2008 and 2009. We describe two new species, Orbinia sagitta n. sp. and Orbinia camposiensis n. sp., and record the occurrences of Orbinia johnsoni (Moore, 1909), which was originally described in California, and Orbinia oligopapillata (López, Cladera & San Martin, 2006), which was previously described from the Pacific coasts of Panama. We provide a key for all the species of Orbinia recorded in the Campos Basin.